Preferences Over Decision-Making - Measures for Advancing Gender Equality (MAGNET) Initiative (International Food Policy Research Institute, 2024)
The Measures for Advancing Gender Equality (MAGNET) initiative aims to broaden and deepen the measurement of women’s agency, based on the development of new tools and rigorous testing and comparison of both new and existing methods for measuring agency, and promoting the adoption of these measures at scale. By increasing the availability of innovative meaningful measures of agency for a broad range of contexts, we hope our work will lead to an improved understanding of what women’s agency is, how it manifests and how it can best be measured across contexts given the research question at hand. Improving women’s decision-making power is crucial for advancing gender equality and is most commonly measured by asking respondents who usually makes decisions over a standard set of domains (e.g., major household purchases, children’s education, health, how earned money is used, etc.). However, interpreting being a decision maker as a proxy of empowerment is only valid if the respondent desires to be involved in the decision. It is not hard to imagine situations in which not being a decision maker reflects an individual acting on their own desires. Understanding preferences and mechanisms behind desired non-involvement provides critical information to inform global initiatives designed to promote women’s decision-making power and agency. This tool, Preferences over Decision-making, aims to capture whether respondents want to be involved in the decisions they are part of and those they are not part of, as well as the reasons for which they might not want to be involved. This tool is suited for nationally representative individual- or household-level surveys, and for targeted thematic or impact evaluation surveys designed to understand women’s agency and decision-making. Other variables you may want to collect alongside this module include marital status and age. This data study includes following files. 1. A survey document (including implementation guidelines)